The seeds of virtue - Horner, D; Horner, David A. (2000)
﻿ There is a prima facie incompatibility between a law conception of ethics, in which law concepts (e.g. ought, rule, action) are basic, and a virtue conception of ethics, in which virtue concepts (e.g. character trait, ideal, agent) are basic. However, both conceptions contain elements that are needed for an adequate ethical account. Aquinas's conception of ethics is of interest, because it combines virtue and law components within a broadly Aristotelian account. I argue that Aquinas's virtue-and-law ethical conception is not ad hoc, but emerges from, expresses, and is grounded normatively, rationally, and motivationally in his general conception of practical thought. My first objective in the thesis is to explicate and defend an interpretation of Aquinas's understanding of practical thought as the rational determination of general good into particular action. I argue, first, that this interpretation expresses Aquinas's conception of the nature of practical thought, as reflected in Aquinas's central practical concepts of order, nature, good, and reason. Second, I argue that this interpretation is expressed in Aquinas's conception of the structure of practical thought, as reflected in general, specific, and particular conceptual levels of practical thinking, reasons, and forms of reasoning. My second objective in the thesis is to show that Aquinas's virtue-and-law account presupposes and develops this conception of practical thought, and briefly to indicate how insights from Aquinas's account elucidate relationships between virtue and law ethical conceptions.